A brief multi-disciplinary review on antimicrobial resistance in medicine and its linkage to the global environmental microbiota - Cantas, Leon; Shah, Syed Q.; Cavaco, Lina M.; Manaia, Célia; Walsh, Fiona; Popowska, Magdalena; Garelick, Hemda; Bürgmann, Helmut; Sørum, Henning (Frontiers in Microbiology, 2013)
The discovery and introduction of antimicrobial agents to clinical medicine was one of the greatest medical triumphs of the 20th century that revolutionized the treatment of bacterial infections. However, the gradual emergence of populations of antimicrobial-resistant pathogenic bacteria resulting from use, misuse and abuse of antimicrobials has today become a major global health concern. Antimicrobial resistance genes have been suggested to originate from environmental bacteria, as clinically relevant resistance genes have been detected on the chromosome of environmental bacteria. As only a few new antimicrobials have been developed in the last decade, the further evolution of resistance poses a serious threat to public health. Urgent measures are required not only to minimize the use of antimicrobials for prophylactic and therapeutic purposes but also to look for alternative strategies for the control of bacterial infections. This review examines the global picture of antibacterial resistance, factors that favor its spread, strategies and limitations for its control and the need for continuous training of all stake-holders i.e. medical, veterinary, public health and other relevant professionals as well as human consumers of antibiotic drugs, in the appropriate use of antimicrobials.